Perilaku Kerja Guru Bimbingan Konseling Laki-Laki dan Perempuan Tingkat SLTA di Jakarta - Esther Widhi Andangsari (Bina Nusantara University, 2010)
Article presented performance behaviour among high school teachers in Jakarta, especially in their roles as counsellor based on the government’s qualification and competences, especially in their empathy and persuasion. The research also wants to see the difference between male and female teachers’ behaviour as counsellor, so that the schools are more serious in selecting and developing their teacher counsellor. Using DISC assessment tool for 68 teachers, consisting of 14 male and 54 female teachers, it is indicated that 26,47% of them meet the government qualification, those are both empathy and persuasion qualifications. Empathy qualification is possessed by male and female teachers, even male teacher is more persuasive than male teacher who have dominant communication behaviour. In general, the research presents 13 behaviour styles.